2020
DOI: 10.1007/s00484-020-01955-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incidence of air quality on human health: a case study on the relationship between pollutant concentrations and respiratory diseases in Kennedy, Bogotá

Abstract: Thousands of deaths associated with air pollution each year could be prevented by forecasting the behavior of factors that pose risks to people's health and their geographical distribution. Proximity to pollution sources, degree of urbanization, and population density are some of the factors whose spatial distribution enables the identification of possible influence on the presence of respiratory diseases (RD). Currently, Bogotá is among the cities with the poorest air quality in Latin America.Specifically, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…It is important to mention that in the months where the greatest amount of minimal outliers were observed for PM10, PM2.5, and O3 concentrations, the highest wind speeds occurred. This according to the monthly historical behavior of wind speed; some researchers reported similar results [14]. Therefore, the results hinted at the influence of wind direction on the occurrence of atypical concentrations or episodes of alert for air pollution in the study megacity.…”
Section: Extreme Pollution Episodessupporting
confidence: 64%
“…It is important to mention that in the months where the greatest amount of minimal outliers were observed for PM10, PM2.5, and O3 concentrations, the highest wind speeds occurred. This according to the monthly historical behavior of wind speed; some researchers reported similar results [14]. Therefore, the results hinted at the influence of wind direction on the occurrence of atypical concentrations or episodes of alert for air pollution in the study megacity.…”
Section: Extreme Pollution Episodessupporting
confidence: 64%
“…The past literature substantiates the adverse effects of air pollution on human health. Researchers found that large portion of deaths are associated with the air pollution that could be reduced by improving the air quality (Molina-Gómez et al, 2020 ). Many health and socio-economic issues are generated from polluted air like cardiovascular and respiratory diseases, visibility issues, economic losses, and climate changes (Etchie et al, 2017 ; Forbes et al, 2009 ; Maione et al, 2016 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Con los grupos etarios que tuvieron IRA y no tuvieron relación con el material particulado y las condiciones meteorológicas, es posible que esto se deba a las aglomeraciones de la población, Santos et al (2019) mencionan que las altas concentraciones de PM10 se presentan en épocas típicas de celebraciones religiosas y culturales de la ciudad de Ocaña. Otras posibles causas son los comportamientos de migración e inmigración (Houston et al, 2020); según la Secretaria de Salud, desde Venezuela y sitios de Colombia arriban al hospital de Ocaña menores de edad y personas con alteraciones en la salud respiratoria; asimismo, mencionan que este tipo de población reside de forma transitoria en la zona norte con crisis alimentaria, económica y de vivienda; adicionalmente, teniendo en cuenta lo explicado por Molina et al (2021), el desplazamiento interno urbano incide en las IRA. De acuerdo con la Secretaria de Planeación de la ciudad de Ocaña, la zona norte es muy frecuentada por su elevado flujo comercial y de transporte.…”
Section: áRea Ambientalunclassified